Indian atom - Sharma, Dhirendra (ed.) (New Delhi, 1986)
We have suffered not so much su advanead technology as much due to fallure and our premises of selance policy. The Indian ATOM examines nuclear arguments for findia on the basis of official documents and critical writings The volume is also meant to be a reference book for legislators, diplomats, critical scientists, political activists, and concerned citizens for safety and environment, it brings together a critical mass of literature including the full text of Atomic Energy Act 1962, the Consti tution of Atomic Energy Commission, and a brief Pakistan Supplement. The emphasis is on the impact of nuclear energy on social and political development of India.
Keywords: Nuclear energy research India